Synthesis and structure of some substituted 2-amino-4-aryl-7-propargyloxy-4H-chromene-3-carbonitriles. Issue 1 (2nd January 2019) - Dinh Thanh, Nguyen; Son Hai, Do; Thi Ngoc Bich, Vu; Thi Thu Hien, Pham; Thi Ky Duyen, Nguyen; Thi Mai, Nguyen; Thi Dung, Tran; Thi Kim Van, Hoàng; Ngoc Toan, Vu; Huy, Nguyen Hung; Thi Thanh Van, Tran; Ngoc Toan, Duong; et al.
Abstract: A series of 2-amino-7-hydroxy-4 H -chromene-3-carbonitriles 4a-l were synthesized through three-component reaction using sodium carbonate as a catalyst. The reaction was carried out in 96% ethanol-water medium (1:20 ratio in volume). Propargyl ether compounds 5a-l of these chromene-3-carbonitriles were successfully synthesized from corresponding hydroxyl chromene derivatives by reaction with propargyl bromide. Two different procedures were applied in this process: the procedure that used potassium carbonate in dried acetone and the procedure that used sodium hydride in dried DMF. The latter gave the ethers 5a-l in higher yields. The single-crystal X-ray structure of propargyl ether 5g has been recorded. Graphical Abstract: